Smartphone-Integrated Automated Sensor Employing Electrochemically Engineered 3D Bimetallic Nanoflowers for Hydrogen Peroxide Quantification in Milk - Kumari R.; Mendki N.; Chandra P. (My University, 2025)
Hydrogen peroxide (H2O2), one of the reactive oxygen species in living beings, serves as a regulator of various cellular processes. However, excessive peroxide concentrations are linked to oxidative stress and promptly disrupt cellular components, leading to several pathological conditions in the body. Moreover, it is extremely reactive and has a limited lifetime; thus, H2O2 sensing remains a prominent focus of research. Enzymatic sensing probes were widely employed to detect H2O2 in the recent past; however, they are susceptible to intrinsic chemical and thermal instabilities, which decrease the reliability and durability of the surface. This research was designed to come up with a feasible solution to this problem. Herein, a novel nonenzymatic peroxidase-mimic three-dimensional (3D) bimetallic nanoflower has been synergistically engineered for quick sensing of H2O2. The sensor platform showed minimal resistance or enhanced charge transfer properties as well as remarkable analytical capability, having a broad linear range between 0.01 and 1 nM and a detection limit of 1.46 ± 0.07 pM. The probe responded to changes in H2O2 concentration in just 2.10 ± 0.02 s, making it a quick sensing platform for H2O2 tracking. This peroxidase-mimic nanozyme probe showed minimal sensitivity to interferants often seen in real-world sample matrices and possessed good recoveries ranging from 92.88 to 99.09% in milk samples. Further, a facile and user-friendly smartphone application (APP) named “HPeroxide-Check” was developed and integrated into the sensor to check the milk adulteration by detecting H2O2. It processes the current output obtained from the sensing interface and provides real-time peroxide concentrations in milk. The entire procedure of fabricating the probe is a single, highly robust step that takes only 10 min and is coupled with a smartphone APP, highlighting the sensor’s quick manufacturing and deployment for automated H2O2 monitoring in industrial and point-of-care settings. © 2024 American Chemical Society.